Penatalaksanaan Perawatan Luka Kanker - Gitarja, Widasari Sri; -, Christina Asmi (Indonesian Journal of Cancer, 2007)
Luka kanker secara psikologis menunjukkan dampak negatif bagi pasien dan juga sulit untuk dirawat, apalagi jika kanker menginfiltrasi ke kulit. Hal tersebut seringkali dikaitkan dengan stadium yang lanjut, jumlah eksudat yang berlebihan dan mudah berdarah. Tujuan utama dari perawatan luka adalah peningkatan kualitas hidup, termasuk didalamnya tidak meninggalkan pengobatan seperti radiasi, khemotherapi, pembedahan dan tentunya perawatan luka.Kata kunci: perawatan, luka kanker, kualitas hidup ABSTRACTMalignant cutaneous wounds are emotionally traumatic and difficult to manage lesion which occour secondary to infiltration of cancer into the skin. This symptom occour in patients with end stage disease and are highly exudative, malodorous, pain, pruritus and bleed easily. As malignant wounds very rarely heal, the aim of management is not wound closure, but rather to promote comfort, prevent social isolation and maintain or improve quality of life. The main goals of treatment are the elimination or control symptoms, which includes radiation, chemotherapy surgery and local wound care.Key Words : care, wound malignant, quality of life